The historical development and challenges of Islam in Ila-Orangun, Nigeria - R Ibrahim Adebayo (Indonesian Journal of Islam and Muslim Societies, 2015)
Like many other Yoruba towns in the south-western Nigeria, Ila-Orangun whichis popularly referred to as the principal town of Igbominaland witnessed thecoming of Islam during a period when paganism had eaten deep into thefabric of every sphere of life of the people. The uniqueness of Islam in thetown is that it has not been able to bring to an end the traditional beliefsystem of the people ever since its inception. This is probably because of thestatus of the town as one of the towns founded by one of the sons of Oduduwafrom the great ancestral land, Ile-Ife. This paper therefore takes a look at theinception of Islam in this ancient town to determine the extent of influenceof traditional belief system on the practice of Islam in it and the methodsadopted by the early Muslim clerics to penetrate the town with a view tobreaking the genes of darkness in the town. Attempts are also made to discusssome latest developments on Islam in town, namely Imamship tussle andother challenges facing the Muslim community there. The paper concludes byidentifying some steps necessary to be taken by the Muslim community in thetown for them to be able to place the religion on a better pedestal.Seperti banyak kota-kota Yoruba lainnya di selatan-barat Nigeria, Ila-Orangunyang populer disebut sebagai kota utama Igbominaland, menyaksikankedatangan Islam selama periode ketika paganisme telah mengakar jauh kedalam setiap bidang kehidupan masyarakat. Keunikan Islam di kota ini adalahbahwa Islam belum mampu membawa pada berakhirnya sistem kepercayaantradisional masyarakat sejak awal. Ini mungkin karena status kota sebagai salahsatu kota yang didirikan oleh salah satu putra dari Oduduwa dari tanah leluhurbesar, Ile-Ife. Oleh karena itu tulisan ini berupaya melihat perkembangan awalIslam di kota kuno ini untuk mengetahui sejauh mana pengaruh sistemkepercayaan tradisional pada praktek Islam di dalamnya dan metode yangdiadopsi oleh para ulama Muslim awal untuk menembus kota dengan maksuduntuk menerobos kegelapan di kota ini. Paper juga berupaya untuk membahasbeberapa perkembangan terbaru tentang Islam di kota ini, yaitu soal ke-imamandan tantangan lain yang dihadapi masyarakat Muslim di sana. Makalah inimenyimpulkan perlunya mengidentifikasi beberapa langkah yang diambil olehkomunitas Muslim di kota ini agar mereka dapat menegakkan agama Islampada alas yang lebih baik.